Precision of wearable heart rate to predict oxygen uptake in endurance vs. sprint-trained runners - Nuno Domingos Garrido; Felipe José Aidar; José Vilaça-Alves; Diogo Roberto Oliveira; Paul Szabo; Victor Machado Reis (Desafio Singular, 2022)
The present study aimed to assess the precision of oxygen uptake with heart rate regression during treadmill running in highly trained runners. Twenty national and international level male runners were divided into two equal groups. Group A was formed of 10 sprinters (31.5± 4.7 years, height 1.74± 0.04 m and mass 61.8± 5.2 kg), and group B comprised 10 endurance runners (25.7± 4.5 years, height 1.77± 0.08 m and mass 71.2± 5.8 kg). Each participant performed six min bouts at a constant velocity on a level treadmill, with each bout at an increased running velocity. The starting velocity was 3.33 m·s-1, with a 0.56 m·s-1 increase in each subsequent bout. VO2 and HR were measured during all runs. Mean peak VO2 and mean peak HR for Group A were, respectively, 71.7± 7.0 mL·kg-1·min-1 and 179.8± 12.7 beats·min-1, while for Group B were 67.3± 4.9 mL·kg-1·min-1 and 198.2± 9.8 beats·min-1. The linearity of the regressions between VO2 and HR in both groups was very high (R2= 0.97 and R2 =0.76) with small standard errors of regression. Despite a stronger correlation in endurance-trained athletes, the results of the present study indicate that it is possible to use HR as an indicator of exercise intensity in individuals trained in both speed and longer distances.